2020
DOI: 10.1007/s00213-020-05454-7
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of value-based decision making behavior by subregions of the rat prefrontal cortex

Abstract: Rationale During value-based decision-making, organisms make choices on the basis of reward expectations, which have been formed during prior action-outcome learning. Although it is known that neuronal manipulations of different subregions of the rat prefrontal cortex (PFC) have qualitatively different effects on behavioral tasks involving value-based decision-making, it is unclear how these regions contribute to the underlying component processes. Objectives Assessing how different regions of the rodent PFC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 42 publications
(67 reference statements)
5
71
0
Order By: Relevance
“…Animal as well as human studies suggest the PFC as the main candidate for updating action and outcome relationship and facilitating flexible learning, while distinct parts of this region contribute to different aspects of learning (Walker et al, 2008;Dalton et al, 2016;Verharen et al, 2020). For example, in a recent rodent study, Verharen et al (2020) demonstrated that pharmacological impairment of the infralimbic cortex and medial OFC resulted in lower punishment learning rates, impairment of prelimbic cortex and lateral OFC was followed by combined negative effects in reward and punishment learning, and overall PFC impairment reduced learning in general.…”
Section: The Neurobiological Mechanismmentioning
confidence: 99%
“…Animal as well as human studies suggest the PFC as the main candidate for updating action and outcome relationship and facilitating flexible learning, while distinct parts of this region contribute to different aspects of learning (Walker et al, 2008;Dalton et al, 2016;Verharen et al, 2020). For example, in a recent rodent study, Verharen et al (2020) demonstrated that pharmacological impairment of the infralimbic cortex and medial OFC resulted in lower punishment learning rates, impairment of prelimbic cortex and lateral OFC was followed by combined negative effects in reward and punishment learning, and overall PFC impairment reduced learning in general.…”
Section: The Neurobiological Mechanismmentioning
confidence: 99%
“…Similarly, the probability of using WSLS strategies across time was~0.5, suggesting these strategies were not used effectively for learning. Indeed, dissociations in learning and WSLS have been reported before [84]. It will be important to investigate the extent to which the later proexploratory phenotype relies on an early attentional decrement, or if these are orthogonal effects of chronic EtOH experience.…”
Section: Sex-independent Etoh Effects On Wsls In Reversal Learningmentioning
confidence: 99%
“…By contrast, CTL rats used a strategy whereby they integrated component processes such as sensitivity to positive and negative feedback, and weighing the benefits of exploration versus exploitation and response persistence. We and others have previously shown that component processes underlying reversal learning require functional activity in PFC regions 19,20 . Thus, the use of a simplified cognitive strategy in SPD rats indicates altered PFC functionality in these animals.…”
Section: Main (Introduction Results and Discussion)mentioning
confidence: 94%
“…S1a-d). We next performed computational trial-by-trial analysis of the behavioural data 20,21 to reveal possible alterations in the component processes subserving probabilistic reversal learning (see Online Methods). The behaviour of CTL rats was best described by a Rescorla-Wagner Q-learning model throughout testing, but the SPD rats came to display behaviour congruent with a simpler heuristic strategy as reversal learning progressed ( Fig.…”
Section: Main (Introduction Results and Discussion)mentioning
confidence: 99%